Student preparation before joining the workforce among part 6 students of FSPPP : A case study in UiTM Melaka City Campus / Nur ‘Aidah Mohd Muzakir and Muhammad Adam Ahmad - Mohd Muzakir, Nur ‘Aidah; Ahmad, Muhammad Adam (Faculty of Administrative Science and Policy Studies, 2013)
Unemployment problem especially among graduates become the major concern in Malaysia. The unemployment among the graduates in Malaysia has been rising recently. This issue need to be curb to avoid the continual number of incensement. Thus, this study identifying the student preparation before joining the workforce among the Part 6 student of UiTM Melaka City Campus. The study was conducted to explore the aspect that lead to inability to secure a job that can help the student and government to deal with the problem. Other than that, it can help government to solve problem from the root especially in high education level. Purposive sampling was used to approach the number of 153 respondents. The respondents consist of UiTM Part 6 students of the year 2013. The questionnaire was distributed to the respondents regarding three aspects which are academic performance, flexibility and skills. The main finding found that skills are the main aspect that should be prepare before joining the workforce. The other aspects are less significant in the data analysis made by using SPSS. The study determines that the graduates need to prepared more on skills to ensure they are available to the job market. Besides, organization nowadays prefers graduates who posses set of skills which are different with others.